PHYSICAL CULTURE IN SCHOOL-AGE CHILDREN (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article provides the necessary information about the development of physical culture of school-aged students in physical education classes, and this thesis is recommended for use as a methodical guide for secondary school teachers.